Resistência à fadiga de um sistema bicamada de porcelana sobre zircônia: efeito das condições de sinterização e tratamento de superfície - Machado, Pablo Soares (2019)
This study is formatted into two parts: the objective of study 1 was to evaluate the influence of the quantity and positioning of feldspathic ceramic over zirconia infrastructure specimens inside the sintering furnace on fatigue strength, color and translucency. Zirconia discs of In Ceram YZ (VITA) were made and sintered (final thickness: 0.7mm, diameter: 15mm). The VITA VM9 (VITA) porcelain was applied, and the specimens were divided into two groups for sintering: G1 group- 20 specimens, sintered one at a time in the center of the furnace; and G5 group- 100 specimens, sintered 5 at a time, 1 in the center of the furnace (G5C) and another 4 in the periphery (G5P). All specimens were ground and polished on the porcelain face until a final thickness of 1.4 mm with zirconia. The specimens were evaluated for color difference and translucency through a spectrophotometer and submitted to the fatigue test (Step-stress, n = 20). Survival rate analysis was performed for fatigue strength, while color and translucency analysis were performed by the CIEDE 2000 parameter. There was no statistical difference between the specimens positioned at the center of the furnace (G5C) and those at the periphery (G5P) for fatigue strength (p = 0.13) and translucency (p = 0.32), just for color (ΔE00> 1.8). Regarding the number of specimens per cycle, there was a statistical difference between the G1 group and the central G5 specimens (G5C) for fatigue strength (p = 0.00) and color (ΔE00> 1.8), but not for translucency (p = 0.26). Study 2 aimed to evaluate the influence of four zirconia surface treatments and thermocycling on the porcelain crack and delamination resistance of a bilayer assembly during fatigue test. Zirconia discs of IPS e.max Zircad MO (Ivoclar) were made, sintered (final thickness: 0.7mm, diameter: 15mm) and randomized into 8 groups (n = 15), according to: ‘surface treatment’ (control - just cleaned; grinding; air-abrasion; and liner application) and ‘thermocycling’ (presence or absence). All specimens were submitted to a roughness test prior to application IPS e.max Ceram (Ivoclar) porcelain and statistically analyzed (Kruskal Wallis). After the porcelain sintering, all specimens were ground and polished on the porcelain face until they had a total thickness of 1.4 mm with zirconia. The thermocycling was performed for the appropriate groups, and the bilayer specimens were then submitted to the fatigue test (Step-stress, n = 15) and survival rate (Kaplen-Meier). The control group was similar to the other treatments for both outcomes, and the liner application treatment presented worse results in relation to the grinding and air-abrasion groups for crack outcome. The outcomes were not affected by thermocycling.